Tindak Ilokusi pada Balasan Tweet @tanyarlfes atas Pernyataan Wamenaker (Kajian Pragmatik) - Wiwik Fitriyani; Devia Reski Novella; Hanum Sa'ada Fidaroeni; Rindiati Amellia Fatikha; Tommi Yuniawan; Qurrota Ayu Neina (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2026)
ABSTRACT This study was conducted with the aim to describe the illocutionary speech acts in the replies of menfess's uploads on social media X @tanyarlfes related to Wamanaker's statement and explain the social and cultural attitudes of the community towards labor issues. This research uses descriptive qualitative method and purposive sampling technique by taking 24 tweet replies as research samples. The data obtained were then categorized according to the types of speech acts and analyzed with the Miles and Huberman analysis model which includes data reduction, data presentation, and conclusion drawing. This study found five types of illocutionary speech acts, namely 8 assertive speech acts, 5 directive speech acts, 1 commissive speech act, 8 expressive speech acts, and 2 declarative speech acts. The forms of illocutionary acts found include speech that aims to convey opinions, command, criticize, and satirize. Keywords: Pragmatic; Social Media, Illocutionary Acts